2015
DOI: 10.1007/s10569-015-9626-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects on satellite orbits in the gravitational field of an axisymmetric central body with a mass monopole and arbitrary spin multipole moments

Abstract: Perturbations of satellite orbits in the gravitational field of a body with a mass monopole and arbitrary spin multipole moments are considered for an axisymmetric and stationary situation. Periodic and secular effects caused by the central gravitomagnetic field are derived by a first order perturbation theory. For a central spin-dipole field these results reduce to the well known Lense-Thirring effects.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The influence of higher spin-multipole moments onto satellite orbits has been discussed in Meichsner and Soffel (2015). Here, it was shown that˙ l=3 LT is less than 0.02 mas/y and hence negligible as are the contributions from other spin multipoles with l ≥ 2.…”
Section: Satellite Motionmentioning
confidence: 88%
“…The influence of higher spin-multipole moments onto satellite orbits has been discussed in Meichsner and Soffel (2015). Here, it was shown that˙ l=3 LT is less than 0.02 mas/y and hence negligible as are the contributions from other spin multipoles with l ≥ 2.…”
Section: Satellite Motionmentioning
confidence: 88%
“…Let us consider a single isolated extended rotating body at rest as source of the gravitational field. The gravitomagnetic acceleration experienced by a test particle orbiting it is (Damour, Soffel & Xu 1994;Meichsner & Soffel 2015)…”
Section: Introductionmentioning
confidence: 99%
“…Effects from higher spinmoments with l > 4 are even smaller (see e.g. Meichsner & Soffel 2015 for related material).…”
Section: The Influence Of Spin-dipole Momentsmentioning
confidence: 99%